Another power of antibody-drug conjugates: immunomodulatory effect and clinical applications - Shi, Ruotong; Jia, Lin; Lv, Zheng; Cui, Jiuwei (Frontiers in Immunology, 2025)
Antibody-drug conjugates (ADCs) enhance tumour immunogenicity through multidimensional immune modulation beyond targeted cytotoxicity. The immune remodelling of the tumour microenvironment (TME) suggests potential synergistic mechanisms with immune checkpoint inhibitors (ICIs): ICIs amplify antitumour immune responses by blocking inhibitory signals. Preclinical studies and preliminary clinical evidence demonstrate their synergistic efficacy; however, mechanistic synergy requires further experimental validation. Current challenges encompass the impact of heterogeneous TME on therapeutic outcomes and toxicity risks including interstitial lung disease. Advancing the translational potential of combination therapies necessitates optimised linker designs, development of immunostimulatory payloads, and establishment of precise biomarker frameworks. This review investigates the immunomodulatory mechanisms of ADCs, providing a theoretical foundation and novel directions for antitumour combination therapies and next-generation ADC development.